IMPLEMENTASI METODE DISCRETE COSINE TRANSFORM (DCT) DAN BLOWFISH DALAM KEAMANAN VIDEO DIGITAL - Siregar, Yunita Sari; Khairani, Mufida; Harahap , Herlina; Lubis, Yessy Fitri Annisa (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Collecting data partially or completely illegally without the permission of the owner causes losses to the copyright owner. This has a big impact in proving ownership of a digital media. To be able to prove ownership of the copyright, the Discrete Cosine Transform watermarking technique can be used by inserting the Blowfish cryptographic algorithm. Discrete Cosine Transform (DCT) is a method that converts digital data into the form of a frequency domain. The method used in the DCT transformation technique is to break the digital image into small blocks with a fixed size and then convert it from the spatial domain to the frequency domain. Blowfish works by dividing the message into 64-bit blocks of equal length with varying aty lengths that encrypt the data in 8 byte blocks. Messages that are not multiples of 8 bytes will be added extra bits (padding), so that the size for each block is the same. After the final result is obtained, the value is inserted into the digital video without destroying the original digital video. From the research that has been done in the implementation of digital video watermarking, it can be concluded that the Blowfish cryptography method and the Discrete Cosine Transform (DCT) watermarking cryptography method can be applied properly. In the watermarking process, digital image insertion does not damage the watermaratd video and at the security level it is provided with blowfish cryptographic encryption, so that it can increase security in copyright protection